2016
DOI: 10.1007/s00405-016-4414-6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity: is really associated with papillary thyroid carcinoma?

Abstract: The incidence of thyroid cancer has been greatly increasing. Several studies aimed to investigate biomarkers for prediction of thyroid cancer. Some of these studies have suggested that thyroid autoantibodies (TAb) could be used as predictors of thyroid cancer risk, but the correlation between TAb and PTC is still a matter of debate. The aim of this study is to evaluate thyroid autoimmunity and TAbs in patients with PTC and benign multinodular goiter (MNG) to investigate if TAbs and autoimmune thyroid disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Overall, these results suggest that unlike TPOAb, TgAb could be a weak but confident predictive marker for PTC in patients presenting with thyroid nodules ( Table 1 ) [ 17 , 20 - 23 , 26 - 30 ]. TgAb may detect newly developed epitopes of Tg derived from thyroid cancer cells.…”
Section: Preoperative Tgab As a Predictor Of Thyroid Cancermentioning
confidence: 93%
“…Overall, these results suggest that unlike TPOAb, TgAb could be a weak but confident predictive marker for PTC in patients presenting with thyroid nodules ( Table 1 ) [ 17 , 20 - 23 , 26 - 30 ]. TgAb may detect newly developed epitopes of Tg derived from thyroid cancer cells.…”
Section: Preoperative Tgab As a Predictor Of Thyroid Cancermentioning
confidence: 93%
“…In contrast, there are some contradictory data; Selek et al and de Alcantara-Jones et al [12,22,23] reported no difference in the prevalence of lymphocyte infiltration or anti-thyroid antibodies between thyroid cancer group and benign tumor group.…”
Section: Studies With Surgical Specimensmentioning
confidence: 98%
“…However, the data on extrathyroidal invasion, lymph node metastasis and prognosis were inconsistent. Some reports showed less extrathyroidal invasion [12,22,29,[48][49][50], but others more [7,19,51] in PTCs with thyroid autoimmunity. Similarly, some showed less lymph node metastasis [12,29,36,48,51,52], but others more [16,18,28,53,54].…”
Section: Is Thyroid Autoimmunity Beneficial For or Harmful Against Thmentioning
confidence: 99%
“…Another widely discussed issue is the connection between thyroid antibodies and cancer [57][58][59]. Some authors reported positive association between anti-thyroid autoantibodies (TgAbs and/or TPOAbs) titers and papillary thyroid cancer (PTC) risk and severity [60,61], however, others question the role of thyroid autoimmunity in thyroid cancer [62]. The large majority of studies reported higher frequency of thyroid antibodies, especially TPOAbs, in breast cancer patients in comparison with healthy controls [59].…”
Section: Clinical Utility Of Tpoabs Testingmentioning
confidence: 99%